2018
DOI: 10.1038/s41598-017-18639-6
|View full text |Cite
|
Sign up to set email alerts
|

A ruthenium-based 5-fluorouracil complex with enhanced cytotoxicity and apoptosis induction action in HCT116 cells

Abstract: Combination of multifunctionalities into one compound is a rational strategy in medicinal chemical design, and have often been used with metallodrug-based compounds. In the present study, we synthesized a novel ruthenium-based 5-fluorouracil complex [Ru(5-FU)(PPh3)2(bipy)]PF6 (PPh3 = triphenylphosphine; and bipy = 2,2′-bipyridine) with enhanced cytotoxicity in different cancer cells, and assessed its apoptosis induction action in human colon carcinoma HCT116 cells. The complex was characterized by infrared, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 30 publications
5
58
0
Order By: Relevance
“…The design of metallodrug-based compounds is an interesting strategy in medicinal chemistry [24] , [25] , [26] , [27] , [28] , [29] , [30] . The most important metallodrug-based compounds are the platinum-based antineoplastic agents.…”
Section: Introductionmentioning
confidence: 99%
“…The design of metallodrug-based compounds is an interesting strategy in medicinal chemistry [24] , [25] , [26] , [27] , [28] , [29] , [30] . The most important metallodrug-based compounds are the platinum-based antineoplastic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Other ruthenium complexes have been previously reported as potent cytotoxic agents, including cyclometalated ruthenium β-carboline complexes, which were cytotoxic to lung, liver, breast, and cervical cancers [ 8 ]; piplartine-containing ruthenium complexes, which were cytotoxic to colon, tongue, liver, breast, skin, and hematological cancers [ 5 ]; a ruthenium complex with xanthoxylin, which was cytotoxic to colon, breast, liver, tongue, gastric, skin, and hematological cancers [ 9 ]; ruthenium imidazole complexes, which were cytotoxic to lung, liver, breast, and cervical cancers [ 19 ]; and, a ruthenium-based 5-fluorouracil complex, which had enhanced cytotoxicity to breast, colon, liver, tongue, skin, and hematological cancers [ 10 ]. The IC 50 values of these compounds are below 10 μM for most of the tested cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium polypyridyl complexes induce apoptosis in BEL-7402 cells through a ROS-mediated mitochondrial dysfunction pathway [ 24 ]. Moreover, the ruthenium-based 5-fluorouracil complex induces caspase-mediated apoptosis in HCT116 cells [ 10 ]. Herein, we observed that the Ru(II)-thymine complex induces caspase-mediated apoptosis in HL-60 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was measured by the Alamar blue assay and was performed as previously described [ 34 , 35 , 36 ]. For all experiments, cells were plated in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%